Hyponatremia: An Unusual Presentation in a Neonate With Chromosome 1q21.1 Deletion Syndrome - Alzarka, Bakri; Usala, Rachel; Whitehead, Matthew T.; Ahn, Sun-Young (Frontiers in Pediatrics, 2018)
Chromosome 1q21.1 deletion syndrome is associated with a wide variety of clinical features including mild to moderate mental retardation, microcephaly, cardiac abnormalities, and cataracts. We report an unusual case of a premature neonate with persistent hyponatremia, markedly elevated plasma arginine vasopressin level (32.7 pg/mL), and clinical findings consistent with the syndrome of inappropriate antidiuretic hormone secretion (SIADH). The patient, who also had microcephaly and dextrocardia, was subsequently diagnosed with chromosome 1q21.1 deletion syndrome. Further evaluation revealed hypothalamic abnormalities, features not previously described with this syndrome. To our knowledge, this is the first report of SIADH associated with congenital hypothalamic anomalies in a neonate with chromosome 1q21.1 deletion syndrome. We also report our experience using tolvaptan, a vasopressin receptor antagonist, in this patient to effectively maintain eunatremia.